So sad but the tobacco boys are...laughing all the way to the bank - Abd Razak, Dzulkifli (2006)
THE Deputy Internal Security Minister enumerated to Dewan Negara last month that among the factors contributing to drug abuse among teenagers were loose religious and family values, lack of sport facilities and poor living environment. But he left out cigarettes — the gateway drug. Given the rather uneventful World No Tobacco Day 2006 celebrated on May 31, this was rather telling. In contrast, a major tobacco company here took the opportunity to highlight its nett profits for the first quarter of the year, which was 20 per cent higher than the previous corresponding period, even though it claimed to be under pressure following tax hikes. In fact, looking ahead, analysts forecast that the earnings for the company are expected to improve compared to that of last year. It is expected to pay "good dividends". In other words, the industry is very much active and influential in determining the health status of many Malaysians.